IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN SIKAP MODERASI BERAGAMA DI SEKOLAH MENENGAH ATAS NEGERI 1 KOTA JAMBI - Romadani; Rusmini; A. A. Musyaffa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the moral challenges faced by contemporary youth, including student violence, intolerance, and the weakening of religious character under the influence of globalization. In a multicultural educational setting such as State Senior High School 1 of Jambi City, where 15% of the 1,054 students are non-Muslim, strengthening religious moderation is essential to prevent radicalism and to foster social cohesion. This research aims to describe the planning and implementation of Islamic Religious Education (PAI) learning in integrating religious moderation values, to analyze its impact on students’ attitudes, and to identify supporting and inhibiting factors in the process. This study employed a qualitative approach with a field research design. Data were collected through structured observations, in-depth interviews with the principal and teachers, and documentation review. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings reveal that lesson planning systematically integrates core values of religious moderation, including tawassuth (middle path), i’tidal (justice), tasamuh (tolerance), and tawazun (balance), into learning objectives, materials, and activities. The implementation is reflected in classroom instruction and school-wide programs such as collective prayers, greeting culture, and faith development activities involving all stakeholders. The results indicate the development of a more harmonious, inclusive, and tolerant school climate. The primary supporting factor is the participatory and exemplary leadership of the principal, while the main constraint is the limited time allocation for Islamic Religious Education subjects.